Multi-colored shades of betalains: recent advances in betacyanin chemistry. Issue 12 (13th September 2021) - Kumorkiewicz-Jamro, Agnieszka; Świergosz, Tomasz; Sutor, Katarzyna; Spórna-Kucab, Aneta; Wybraniec, Sławomir
Abstract : The updated classification of all known betacyanin plant pigments and a review of the current research focused on the chemical properties of the pigments are presented, in addition to the description of semi-synthesis of betalamic acid conjugates. Abstract : Covering: 2001 to 2021 Betacyanins cover a class of remarkable natural red-violet plant pigments with prospective chemical and biological properties for wide-ranging applications in food, pharmaceuticals, and the cosmetic industry. Betacyanins, forming the betalain pigment group together with yellow betaxanthins, have gained much attention due to the increasing social awareness of the positive impact of natural products on human health. Betalains are commercially recognized as natural food colorants with preliminarily ascertained, but to be further investigated, health-promoting properties. In addition, they exhibit a remarkable structural diversity based on glycosylated and acylated varieties. The main research directions for natural plant pigments are focused on their structure elucidation, methods of their separation and analysis, biological activities, bioavailability, factors affecting their stability, industrial applications as a plant-based food, natural colorants, drugs, and cosmetics as well as methods for high-yield production and stabilization. This review covers period of the last two decades of betacyanin research. In the first part of the review, we present an updated classification of all known betacyanins and their derivatives identified by chemical means as well as by mass spectrometric and NMR techniques. In the second part, we review the current research reports focused on the chemical properties of the pigments (decarboxylation, oxidation, conjugation, and chlorination reactions as well as the acyl group migration phenomenon) and describe the semi-synthesis of natural and artificial fluorescent betalamic acid conjugates, showing various prospective research directions.